Finite element analysis over transmission region of coronavirus in CFD analysis for the respiratory cough droplets - Supriya Devi; K.V. Nagaraja; L. Thanuja; M.V. Reddy; S Ramakrishna (Ain Shams Engineering Journal, 2022)
The pandemic outbreak of COVID-19 is worldwide now which requires a novel solution to control the fast-spreading virus. The coronavirus analysis over the contaminated area and its speed of transmission if examined can prevent the spread of COVID-19. A wide range of such problems could be simplified through finite element analysis for a better solution. Many computational fluid dynamics problems could be solved by the finite element method (FEM) effectively by utilizing finite elements. A remarkable linear triangular element meshing over the transmission region between the individuals has been generated by triangular unstructured meshes to analyze the velocity of the virus. The flow intensity of the coronavirus has been analyzed within the standard specified distance recommended by WHO between two individuals at 1.83 m to hinder the spread of COVID-19. Extended work has fabulously extracted the element and nodal information from the discretization region. Moreover, it has been effectively utilized to simplify the numerical solutions of FEM and improve its efficiency to a larger extent. We have discretized the region of transmission of respiratory cough droplets carrying coronavirus from an infected person and the intensity and the speed of the transmission have been computed. The velocity of the transmission of coronavirus has been analyzed by solving an elliptical partial differential equation (PDE) over the region around the mask of an infected individual at a specified distance of 1.83 m. Infectious transmission of COVID-19 in different environmental conditions is of numerous complexities to work on and analyze the growth of the infectious coronavirus. Mathematical models formulated for respiratory cough droplets carrying coronavirus can be very efficiently simplified through FEM when the information of the velocity of flow and existence of the coronavirus at the particular stage of transmission region is known. The present study of different temperatures and analysis of wind factors during the transmission process can help to reduce the infection risk between individuals if the recommended specified distance is maintained within the individuals. It is very helpful to formulate and implement a suitable guideline for this pandemic time.